A light and scanning electron microscopic diagnosis of leaf epidermal morphology and its systematic implications in Dryopteridaceae: Investigating 12 Pakistani taxa. (August 2018) - Shah, Syed Nasar; Ahmad, Mushtaq; Zafar, Muhammad; Malik, Khafsa; Rashid, Neelam; Ullah, Fazal; Zaman, Wajid; Ali, Maroof
Highlights: First detailed microscopic diagnosis by LM and SEM of foliar epidermis in two genera of Dryopteridaceae. The taxonomic implications of foliar epidermal anatomy in 12 species of Dryopteridaceae were studied. Evaluation of the contribution of leaf epidermal anatomy to the delimitation of genera and species on the basis of morphometric analysis. Abstract: Dryopteris and Polystichum are the 2 complex taxonomic genera of Dryopteridaceae. The comparative foliar epidermal anatomy of 12 species of both genera from Pakistan were studied using standard protocols of light microscopy (LM) and scanning electron microscopy (SEM). The objective of which was systematic comparison and investigation to elucidate the taxonomic importance of foliar micromorphology, which may be useful to taxonomists for identifying complex Dryopteridaceae taxa. Principal component analysis and UPGMA clustering analysis were performed to test the validity of leaf anatomical features as method of separating species and genera. The foliar epidermal anatomy described here is a good source of taxonomic characters in both groups that can help genera and species delimitation. This is the first report on leaf micromorphology in most of these species. Observation of foliar anatomy showed that stomata are only present on the abaxial surface; i.e., leaves of all species are hypostomatic. The shapes of epidermal cells in all studied species are irregular. The anticlinal walls are strongly lobed, irregular wavy and elongated wavy. However, substantial variation in epidermal cell size and other stomatal features were observed on both upper and lower surfaces in all investigated species. Two types of stomata were observed in all studied species. The presence of polocytic stomata in Dryopteris and staurocytic stomata in Polystichum are the important characters for the segregation of these genera. Elongate elliptic stomatal shape, narrow kidney shaped guard cells and broad elliptic shaped stomatal pores are diagnostic for all five species of Dryopteris selected. On the other hand, size and number of epidermal cells, lobes per cell, stomatal size, subsidiary cell size, stomatal pore size and stomatal index are the key features for species differentiation in Polystichum . An identification key was developed in order to apply the foliar anatomical characters in the discrimination of the species studied.